Linking bone development on the caudal aspect of the distal phalanx with lameness during life - Newsome, R.; Green, Martin J.; Bell, N.J.; Chagunda, M.G.G.; Mason, C.S.; Rutland, Catrin S.; Sturrock, Craig; Whay, H.R.; Huxley, J.N. (American Dairy Science Association, 2016)
Claw horn disruption lesions (CHDL; sole hemorrhage, sole ulcer, and white line disease) cause a large proportion of lameness in dairy cattle, yet their etiopathogenesis remains poorly understood. Untreated CHDL may be associated with damage to the internal anatomy of the foot, including to the caudal aspect of the distal phalanx upon which bone developments have been reported with age and with sole ulcers at slaughter. The primary aim of this study was to assess whether bone development was associated with poor locomotion and occurrence of CHDL during a cow’s life. A retrospective cohort study imaged 282 hind claws from 72 Holstein-Friesian dairy cows culled from a research herd using X-ray micro–computed tomography (μ-CT; resolution: 0.11 mm). Four measures of bone development were taken from the caudal aspect of each distal phalanx, in caudal, ventral, and dorsal directions, and combined within each claw. Cow-level variables were constructed to quantify the average bone development on all hind feet (BD-Ave) and bone development on the most severely affected claw (BD-Max). Weekly locomotion scores (1–5 scale) were available from first calving. The variables BD-Ave and BD-Max were used as outcomes in linear regression models; the explanatory variables included locomotion score during life, age, binary variables denoting lifetime occurrence of CHDL and of infectious causes of lameness, and other cow variables. Both BD-Max and BD-Ave increased with age, CHDL occurrence, and an increasing proportion of locomotion scores at which a cow was lame (score 4 or 5). The models estimated that BD-Max would be 9.8 mm (SE 3.9) greater in cows that had been lame at >50% of scores within the 12 mo before slaughter (compared with cows that had been assigned no lame scores during the same period), or 7.0 mm (SE 2.2) greater if the cow had been treated for a CHDL during life (compared with cows that had not). Additionally, histology demonstrated that new bone development was osteoma, also termed “exostosis.” Age explained much of the variation in bone development. The association between bone development and locomotion score during life is a novel finding, and bone development appears specific to CHDL. Bone development on the most severely affected foot was the best explained outcome and would seem most likely to influence locomotion score. To stop irreparable anatomical damage within the foot, early identification of CHDL and effective treatment could be critical.